Conceptual preliminary design of a transplanting machine at the main nursery / Mohd Azwa Afifie Rosland - Afifie Rosland, Mohd Azwa (Faculty of Plantation and Agrotechnology, 2016)
Oil palm (Elaeis guineensis) is the most productive oil crop compared to the others major oil crops such as soy beans and sunflower. As the importance of this crop as the main economic contributors, good nursery management would be required to ensure the production of uniformly good and healthy seedlings from a nursery in order to achieve early bearing high yields in the field. In the double stage nursery, transplanting is one of the main process but there are many shortcoming from the conventional method that will decreased the productivity of work to be done. As the problem give a huge impact, a design concept of transplanting machine will be designed to fulfill the need. The concept design of the oil palm nursery transplanting machine for the main nursery polybag might be able to help in improving the field efficiency in the oil palm nursery compared to the conventional method in the transplanting process. With the ability to work independently and faster compared to the man power, transplanting work in the main nursery will no longer considered as the most drudgery work in the nursery.